2010
DOI: 10.4236/health.2010.29151
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer screening program based on HPV testing and conventional Papanicolaou cytology for jail inmates

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…There is a paucity of data in HPV testing among incarcerated women in low resource countries. Most studies describing the epidemiology of hr-HPV infection among incarcerated women have emanated from relatively higher-income settings [10][11][12][13][14][15][16]. In lower income settings, studies have been done using non-routine clinical approaches [10,12,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…There is a paucity of data in HPV testing among incarcerated women in low resource countries. Most studies describing the epidemiology of hr-HPV infection among incarcerated women have emanated from relatively higher-income settings [10][11][12][13][14][15][16]. In lower income settings, studies have been done using non-routine clinical approaches [10,12,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The range of publication dates was wide with studies performed between 1968 and 2017. Included studies were from USA,25–37 Canada,38–42 UK,43–47 Spain,48 49 Italy,50 Brazil,51–54 Peru,55 Mexico,56 57 Taiwan58 and Russia 59. All studies had a cross-sectional design and only nine included a comparison group.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies reported the prevalence of HPV genital infection in imprisoned women using molecular detection methods 28 48–50 52 53 58 59. None of these studies had a comparison group, and there were no available data from national screening programmes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated 470000 new cases of infection and about 230000 deaths per year represents a global challenge, especially in under-developed countries, where cervical cancer is the leading cause of death from cancer ( 2 ). It is believed that infection with human papillomaviruses (HPVs) is necessary for development of cervical cancer ( 3 ). This infection, which is one of the most common Sexually Transmitted Infections (STIs) worldwide ( 4 ), not only contributes to the etiology of cervical cancer, especially in the case of high-risk HPV types (HPV 16, 18, 31, 33, etc.…”
Section: Introductionmentioning
confidence: 99%